Pelatihan Pemanfaatan Media Pembelajaran Matematika berbasis Augmented Reality dengan Platform Assemblr Bagi Guru SMP Lombok Barat - Nilza Humaira Salsabila; Hapipi Hapipi; Nurul Hikmah; Gilang Primajati; Pratama Wahyu Purnama; Ashri Abdiah (Rengganis Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to enhance teachers' competencies in developing and implementing geometry learning media based on Augmented Reality (AR) using the Assemblr platform. The implementation method consisted of three stages: preparation, implementation, and evaluation. The preparation stage included a needs analysis of participants and the development of training materials. The implementation stage involved the delivery of materials on the concept of Augmented Reality in mathematics education and demonstrations of the use of the Assemblr platform. The evaluation stage was conducted by collecting participants' responses to the training activities. The results indicated that the participants were able to understand the basic concepts of Augmented Reality and utilize simple geometry learning media developed using the Assemblr platform. In addition, participants provided positive responses regarding the training materials, delivery methods, and the usefulness of AR technology in supporting geometry learning. The activity successfully improved teachers' knowledge and skills in utilizing digital technology as a learning medium. Therefore, training on the use of the Assemblr platform can serve as an effective alternative for supporting the development of more interactive and innovative geometry learning media in junior high schools.